2017
DOI: 10.1111/apa.14158
|View full text |Cite
|
Sign up to set email alerts
|

The effect of skin‐to‐skin care on cerebral oxygenation during nasogastric feeding of preterm infants

Abstract: Cerebral oxygenation remained stable before, during and after gavage feeding in an incubator and during skin-to-skin care. The small decrease in oxygen saturation whilst receiving gavage feeding during skin-to-skin care is unlikely to be clinically important, providing reassurance that preterm infants maintain physiological stability during skin-to-skin care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 24 publications
1
15
1
Order By: Relevance
“…Promotion of SSC is one mechanism by which nurses can help mothers in the provision of human milk so that mothers and infants achieve breastfeeding. For those infants not ready to orally feed, SSC has been found to be as safe as incubator care during gavage feedings, with no significant differences found in cerebral oxygenation, heart rate, or oxygen saturation (Marulli et al, 2018).…”
Section: Ssc and Feedingmentioning
confidence: 99%
“…Promotion of SSC is one mechanism by which nurses can help mothers in the provision of human milk so that mothers and infants achieve breastfeeding. For those infants not ready to orally feed, SSC has been found to be as safe as incubator care during gavage feedings, with no significant differences found in cerebral oxygenation, heart rate, or oxygen saturation (Marulli et al, 2018).…”
Section: Ssc and Feedingmentioning
confidence: 99%
“…KMC, kangaroo mother care; SpO 2 , oxygen saturation; HR, heart rate; rScO 2 , regional cerebral oxygenation; FtOE, fractional tissue oxygen extraction; FiO 2 , fraction of inspired oxygen. requirement of noninvasive respiratory support and FiO 2 [13,14,25,26,28].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have focused on the analysis of the possible benefits in brain oxygenation during KC [7, 8, 17, 27, 29, 34, 36, 37]. Two studies employed INVOS (Medtronic, Minnesota, USA) (30,37), three employed Fore-Sight (Edwards LifeScience, California, USA) [7, 8, 17], and one study employed SenSmart X-100 (NONIN Medical, Stockholm, Sweden) [34]. Lorenz et al [8] showed a significant increase ( p < 0.01) in rScO 2 during KC (74.8% ± 4.6%) versus incubator care (73.6% ± 6.0%).…”
Section: Discussionmentioning
confidence: 99%
“…Only few studies [7, 8, 17, 29, 33] and with a low degree of evidence have analyzed FtOE during KC. Studies reported that FtOE was within the normal range and remained stable during KC and incubator care independently of the requirement of respiratory support [7, 8, 17, 33, 34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation